Fifth toe Fillet Flap for Wound Coverage of Non-Healing Ulcer of the Foot: Surgical Technique and a Case Report - Chaudhary, Sunny; Bali, Shivakumar A; Singh, Arvind; Siddharth, R K (Asian Journal of Medical Research, 2020)
Fillet flap is one of the options in the treatment of diabetic non-healing ulcers. The advantages of the fillet flap include the absence of donor site morbidity, excellent durability and preventing the need for more proximal amputation. A 56-year-old farmer presented to the out-patient department with complaints of a non-healing ulcer on the sole of the right foot for the past 7 months which was managed conservatively. A fifth ray partial amputation and a rotational flap of the redundant fifth finger for wound coverage were done. The wound healing was uneventful and the sutures were removed after two weeks. At the latest follow-up of 2 years, the patient was able to walk independently without pain and without any functional limitations. This case report describes the surgical technique of the lateral lesser toe fillet flap for wound closure on the plantar aspect of foot as an alternative to secondary healing or more proximal amputations.